ANALYSIS OF SURFACE DEFECTS OF ALUMINUM AND ITS ALLOYS WITH A SCANNING KELVIN PROBE - A. K. Tyavlovsky; A. L. Zharin; O. K. Gusev; R. I. Varabei; N. I. Muhurov; G. V. Sharonov; K. U. Pantsialeyeu (Приборы и методы измерений, 2017)
Currently, the use of probe electrometry in non-destructive testing is constrained by the complexity of measurement results interpretation. An output signal of electrometric probe depends on a number of physical and chemical parameters of surface including chemical composition variations, stresses, dislocations, crystallographic orientation of a surface, etc. The study aims to the use of probe electrometry methods for nondestructive testing and analysis of precision metal surfaces’ defects after different treatment or processing.Control of surface defects of aluminum and its alloys was performed with a scanning Kelvin probe technique. The results of scanning were plotted in a form of contact potential difference (CPD) distribution map. Additionally, a histogram of CPD values distribution and statistical characteristics including the expectation of CPD mean value and histogram half-width were calculated either for the whole distribution or for each individual mode in a case of multimodal distribution.The spatial CPD distribution of A99 aluminum and AMG-2 alloy surfaces after electrochemical polishing and diamond finishing was studied. An additional study was held for AMG-2 surface after the formation of 30 microns thick specific nanostructured alumina oxide surface layer. Higher quality surfaces have characterized as more homogeneous distribution of the physical properties (at half-width distribution histogram). Surfaces with higher mechanical strength and overall better mechanical properties found to have lower CPD values that correspond to higher electron work function and surface energy. The presence of the second mode in the CPD distribution histogram indicates the significant proportion of defect areas on the sample surface.Analysis of visualized CPD distribution maps using defined criteria allows detecting and characterizing such defects as residual stress areas, areas with reduced microhardness, surface contamination spots, corrosion defects. This provides the possibility of rapid nondestructive testing and diagnostic of precision metal surfaces, in particular the starting substrates for sensitive elements and sensory devices manufacture.